Anomalous reduction of the switching voltage of Bi-doped Ge0.5Se0.5 ovonic threshold switching devices - Seo, Juhee; Ahn, Hyung-Woo; Shin, Sang-yeol; Cheong, Byung-ki; Lee, Suyoun (AMER INST PHYSICS, 2014)
Switching devices based on Ovonic Threshold Switching (OTS) have been considered as a solution to overcoming limitations of Si-based electronic devices, but the reduction of switching voltage is a major challenge. Here, we investigated the effect of Bi-doping in Ge0.5Se0.5 thin films on their thermal, optical, electrical properties, as well as on the characteristics of OTS devices. As Bi increased, it was found that both of the optical energy gap (E-g(opt)) and the depth of trap states decreased resulting in a drastic reduction of the threshold voltage (V-th) by over 50%. In addition, E-g(opt) was found to be about three times of the conduction activation energy for each composition. These results are explained in terms of the Mott delocalization effect by doping Bi. (C) 2014 AIP Publishing LLC.
Keywords: CHALCOGENIDE-GLASS; THIN-FILMS; SEMICONDUCTORS; MECHANISM; SYSTEMS